The eat fat, get thin cookbook : more than 175 delicious recipes for sustained weight loss and vibrant health - Hyman, Mark, 1959- (Little, Brown and Company, 2016)
Hyman believes that the key to losing weight and achieving ultimate health is to eat more fat, not less. He shares gluten-free recipes that support this lifestyle, yet will satisfy even the pickiest eaters in your family. You'll also get meal plans, tips and tricks, and helpful guides to stocking your fridge and pantry.